Mininet-GUI: Uma Abordagem Visual e Interativa para Experimentação em Redes SDN - Schneider, Lucas M.; P. Neto, Emídio; Silva, Felipe S. Dantas (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2025)
Mininet is a widely adopted emulator for prototyping and experimenting with Software-Defined Networking (SDN). Its main graphical interface, MiniEdit, however, offers limited functionality and low interactivity, which hampers adoption and constrains advanced experimentation. Although several alternative tools have been proposed, none has become a definitive replacement, largely due to the absence of essential integrated features. We present Mininet-GUI, a web-based tool that enables real-time creation, editing, and execution of Mininet topologies. Mininet-GUI allows dynamic manipulation of hosts, switches, controllers, and links, as well as direct command execution through the interface. Unlike existing approaches, it provides interactive topology editing, simplified terminal access via WebShell, and support for exporting and importing topologies in JSON and Python formats. Mininet-GUI is designed to make SDN experimentation more accessible and efficient for both beginners and advanced researchers. This paper describes its architecture, capabilities, and applicability through common use cases.